Elements of progressive personal income taxation in the context of the principle of forward and backward links - N. M. Artemov; К. A. Ponomareva (Правоприменение)
The idea of progressive tax scale in Russia received a fundamentally new development in 2020. The leading position of the personal income tax in most countries is due to a number of circumstances. First, it is a personal tax, the object of which is the income actually received by the payer, and not the estimated average income that could be received in specific economic conditions. Second, income tax allows to maximize the implementation of the basic principles of taxation – universality and uniformity. In recent decades, national regimes of personal income taxation regimes have been actively developed both in foreign countries and in Russia. Purpose of the study. The article considers the elements of progressive taxation of personal income in the context of the principle of direct and inverse relations. Dealing with selected provisions of the national legislation of European countries and Russia the article shows that elements of progressive taxation can be applied only in particular aspects. The proposals of taxation of rich taxpayers are also brought into light. Methodology. The research was carried out with the application of the formally legal interpretation of legal acts as well as the comparative analysis of Russian and European legal literature. Structural and systemic methods are also the basis of the research, The main results. The establishment of a classical progressive system in the Russian Federation will encourage a change in the model of behavior of both persons who have the opportunity to increase their income, but do not intend to do so due to a decrease in the nominal increase in wages, and persons who previously declared income in full, but if the tax model changes, they will apply personal income tax evasion schemes. In addition, the results of a comparative analysis of the experience of the EU Member States show the ineffectiveness of the progressive income tax scale as a tool to combat social inequality. The comparison provided in the research also examines the problems of proportional and progressive taxation in the context of the principle of equity. In the context of the practice of applying progressive taxation, the experience of foreign countries is studied. Based on foreign experience, it can be concluded that the introduction of family taxation would require a fundamental change in the basis of income taxation in the Russian Federation, as well as would entail discrimination of taxpayers in terms of registered and civil marriage and abuse in order to extract tax benefits. The authors conclude that a more appropriate option for taking into account family circumstances is the widespread use of tax deductions. Since Russian legislation does not establish poverty criteria, personal income tax is levied even on income in the amount of the subsistence minimum. This also does not correspond to the principle of social justice, because in the absence of such criteria, poverty cannot be considered a basis for tax exemption. Thus, the establishment of a classical progressive system in the Russian Federation will encourage a change in the model of behavior of both persons who have the opportunity to increase their income, but do not intend to do so due to a decrease in the nominal increase in wages, and persons who previously declared income in full, but if the tax model changes, they will apply personal income tax evasion schemes. We believe that in the context of the principle of equity, the essence of progressive taxation is not the establishment of several tax rates and is not determined by the number of tax deductions that can be granted only to a small number of persons, including wealthy taxpayers, but that it reflects the ability of a person to pay tax. In our opinion, this ability should be guaranteed by the exemption from taxation of the minimum amount of income (minimum wage). Сonclusions. According to the results of the study, it is concluded that the establishment of a classical progressive system in the Russian Federation will encourage a change in the behavior model of both persons who have the opportunity to increase their income, but do not intend to do so due to a decrease in the nominal increase in wages, and persons who previously declared income in full, but if the tax model changes, they will use personal income tax evasion schemes. In addition, the results of a comparative analysis of the experience of the EU member States show the ineffectiveness of the progressive income tax scale as a tool to combat social inequality. It is proposed to apply only elements of progressive taxation when reforming the Russian tax regime for individuals, namely, to establish a nontaxable minimum in the amount of the minimum wage, which will ensure tax fairness for taxpayers with lower-average incomes.